The Human Body: Hearing, Taste and Smell: patways of perception - Whitfield, Philip; Marshall, Bruce; Johnson, Jinny (New York : Torstar Books, 1984)
La serie The Human Body cuenta con cuatro ejemplares en donde cada uno nos enseña de una manera diferente cada parte del cuerpo
1. The functioning of the Ear 2. Sound and Hearing 3. The imperfect ear 4.The versatile toungue 5. Sweet, Sour, Salt, Bitter and others
Incluye índice
Keywords: EL CUERPO HUMANO; GUSTO; OLFATO; AUDICIÓN